Scheduling in stochastic flowshops with independent setup, processing and removal times - (:unkn) unknown (Elsevier Ltd, 1997)
The two-machine flowshop problem, where setup and removal times are independent from processing times and machines suffer stochastic breakdowns, is considered with respect to makespan performance measure. After the problem is formulated, an objective function for the makespan is developed. Under certain conditions on the breakdown processes, it is shown that Sule and Huang's [5] algorithm for the deterministic problem stochastically minimizes makespan for the stochastic counterpart problem. © 1997 Elsevier Science Ltd.